Matrix metalloproteinases (MMPs), the main extracellular matrix (ECM) enzymes in collagen degradation, as a target for anticancer drugs. (1st November 2016) - Jabłońska-Trypuć, Agata; Matejczyk, Marzena; Rosochacki, Stanisław
Abstract: The main group of enzymes responsible for the collagen and other protein degradation in extracellular matrix (ECM) are matrix metalloproteinases (MMPs). Collagen is the main structural component of connective tissue and its degradation is a very important process in the development, morphogenesis, tissue remodeling, and repair. Typical structure of MMPs consists of several distinct domains. MMP family can be divided into six groups: collagenases, gelatinases, stromelysins, matrilysins, membrane-type MMPs, and other non-classified MMPs. MMPs and their inhibitors have multiple biological functions in all stages of cancer development: from initiation to outgrowth of clinically relevant metastases and likewise in apoptosis and angiogenesis. MMPs and their inhibitors are extensively examined as potential anticancer drugs. MMP inhibitors can be divided into two main groups: synthetic and natural inhibitors. Selected synthetic inhibitors are in clinical trials on humans, e.g. synthetic peptides, non-peptidic molecules, chemically modified tetracyclines, and bisphosphonates. Natural MMP inhibitors are mainly isoflavonoids and shark cartilage.